Psychology and religion: an introduction - Argyle, Michael (Routledge, 2000)
Should psychology try to explain religion or try to understand it? The author of this book ranges over the whole of psychology to look at the results of psychology's study of religion. His belief in both the empirical value of psychology and the spiritual value of religion are evident.